PENGARUH SOSIALI PERPAJAKAN, PELAYANAN FISKUS, SANKSI PERPAJAKAN, KESADARAN WAJIB PAJAK, DAN PENGETAHUAN PAJAK TERHADAP KEPATUHAN MEMBAYAR PAJAK WAJIB PAJAK ORANG PRIBADI (Studi Kasus Pada Wajib Pajak Orang Pribadi Non Karyawan Yang Terdaftar di KPP) - Iis Alafiyah, 11.05.52.0047; Maryono, Maryono (Students Journal of Accounting and Banking, 2016)
This study aimed to analyze the effect of tax socialisation, fiskus service, tax penalties, awareness taxpayers, tax knowledge, and tax verification to obidience of individual taxpayers. The population in this study is the population in this study are all individual taxpayers who perform independent activities listed on KPP Batang. Methods of data analysis used in this study were using multiple linear regression analysis to test the hypothesis using the t test. Before using multiple regression analysis, to test the validity, reliability, normality, classical assumption test and multiple regression. The results showed that the socialization of tax and service tax authorities had no significant effect on tax compliance. While tax penalties, consciousness of paying taxes, tax knowledgae of significant positive effect on tax compliance. Â Keywords: Socialization Tax, Service Tax Authorities, Tax Penalties, Awareness Taxpayers, Knowledge of Tax, Obidience Tax Payers